Strategi Dakwah Masjid Agung Ibnu Batutah dalam Meningkatkan Nilai Keagamaan Umat Islam di Kawasan Lima Rumah Ibadah Beda Agama Puja Mandala Kuta Selatan Badung Bali - Fitria, Tarisha Nur; Al Ahsani, Nasirudin (Fakultas Dakwah UIN KHAS Jember, 2023)
Islam is a minority religion on the island of Bali, with a population comprising only 10% of the overall Balinese society. In its existence as a minority religion, the Muslim community must certainly adapt to Bali's indigenous culture in religious activities to maintain religious tolerance. This is related to the religious values of Muslims in Bali, which are questioned whether they are increasing or decreasing. The purpose of this research is: a) to identify and describe the propagation strategies of the Ibnu Batutah Grand Mosque in enhancing the religious values of Muslims in the Puja Mandala area; b) to identify and describe the increase in religious values of Muslims at the Ibnu Batutah Grand Mosque. In this study, the author employs a qualitative approach with descriptive research. Based on the research findings, it can be concluded that: a) the propagation strategy in enhancing the religious values of Muslims, especially in Puja Mandala, involves creating programs consisting of educational activities, worship activities, community social activities, and socio-economic activities. These activities are further divided into several fields implemented on a daily, weekly, and monthly basis. b) the religious values of Muslims at the Ibnu Batutah Grand Mosque have increased, as each propagation program contains indicators for increasing values, namely creed, Sharia, and morality.